Ectopic localization of autophagosome in fatty liver is a key factor for liver regeneration. (2nd January 2019) - Matsumoto, Yoshihiro; Yoshizumi, Tomoharu; Toshima, Takeo; Takeishi, Kazuki; Fukuhara, Takasuke; Itoh, Shinji; Ikegami, Toru; Soejima, Yuji; Mori, Masaki
ABSTRACT: Autophagy has a critical role in liver regeneration. However, no studies have demonstrated autophagic flux in the regenerating fatty liver. The aim of this study was to clarify the dynamics of autophagy in the regeneration of the fatty liver. Following 70% partial hepatectomy (PH) in db/db fatty mice, which is a non-alcoholic fatty liver disease (NAFLD) model, we investigated the survival rate and recovery of liver volume. Histological examination of the regenerating liver was examined using electron microscopy. The 7-day survival rate after PH in db/db mice was 20%, which was significantly lower than that in control mice ( P < .01). Liver regeneration within 48 h after PH was significantly impaired in db/db mice ( P < .05). The number of proliferating cell nuclear antigen (PCNA) positive cells and the expression levels of cell-cycle markers cyclins D, E, and A were lower in db/db mice compared with controls. In the regenerating liver, LC3-II level was higher in db/db mice, but p62 expression was increased and cathepsin D expression, a marker of autophagolysosome proteolysis, was decreased compared with controls. Additionally, electronic microscopy revealed that autophagosomes during liver regeneration in db/db mice were mainly located in lipid droplets. Our findings indicate that the different localization of autophagosomes in db/db mice compared with controls led to impairment of liver regeneration in the fatty liver.